Temporomandibular disorders, pain in the neck and shoulder area, and headache among musicians - van Selms, Maurits K. A. (J Oral Rehabil, 2019)
BACKGROUND: Uncertainties still exist about the role of playing musical instruments on the report of musculoskeletal complaints and headache. OBJECTIVES: To evaluate the prevalence of and risk indicators for symptoms of temporomandibular disorders, pain in the neck or shoulder, and headache among musicians. METHODS: A questionnaire was distributed among 50 Dutch music ensembles. RESULTS: The questionnaire was completed by 1470 musicians (response rate 77.0%). Of these, 371 musicians were categorised as woodwind players, 300 as brass players, 276 as upper strings players, 306 as vocalists and 208 as controls; nine musicians had not noted their main instrument. The mean age was 41.6 years (standard deviation [SD] 17.2), and 46.5% were male. Irrespective of instrumentalist group, 18.3% of the musicians reported TMD pain, 52.5% reported pain in the neck and shoulder area, and 42.5% reported headache. Of the functional complaints, 18.3% of the musicians reported TMJ sounds, whereas a jaw lock or catch on opening or on closing was reported by 7.1% and 2.4%, respectively. TMD pain was associated with playing a woodwind instrument, whereas pain in the neck and shoulder was associated with playing the violin or viola. For each complaint, oral behaviours were found as risk indicator, supplemented by specific risk indicators for the various complaints. CONCLUSIONS: The current finding that pain‐related symptoms varied widely between instrumentalist groups seems to reflect the impact of different instrument playing techniques. Playing a musical instrument appears not the primary aetiologic factor in precipitating a functional temporomandibular joint problem.